Mechanical Properties of Concrete Containing River Indus Sand and Recyclable Concrete Aggregate - Lakhiar, Muhammad Tahir; Mohamad, Noridah; Jhatial, Ashfaque Ahmed; Sohu, Samiullah; Oad, Mehboob (Salehan Institute of Higher Education, 2018)
In Pakistan construction Industry, concrete construction is cheaper than the other construction methods with respect to that construction materials demand rises. The 75% volume of total concrete fill with aggregate which contributes to decrease the natural aggregate resources day by day. The best solution for this problem is to utilize River Indus sand and recyclable concrete aggregate as fine and coarse aggregate respectively. In this research the River Indus sand and recyclable coarse aggregate were fully replaced with normal aggregates. The aim of this study was to examine the flexural and tensile performance of concrete containing the River Indus sand and recyclable concrete aggregate. The physical properties were also examined which include the sieve analysis and chemical composition of River Indus sand. The M15, M20 and M25 grade were analyzed at 7, 14, 21 and 28 days water curing. The results define that, flexural strength was reduced from 5% to 15% compared to normal aggregate whereas tensile was decreased from 1% to 1.8% at 28 days water curing.